THE ROLE OF WORK SATISFACTION AS INTERVENING VARIABLE IN THE INFLUENCE OF EMPLOYEE ENGAGEMENT AND COMPETENCY TO PERFORMANCE - Priyono, Bambang Suko; Lestari, Lilik; Liana, Lie (Proceeding Fakultas Ekonomi, 2017)
This research is aimed to analyze the role of work satisfaction in the influence of employee engagement and competency to performance.  This study is conducted on employees of a hospital in Central Java, Indonesia. One hundred respondents were taken by using simple random sampling method. Structural Equation Model (SEM) is used as an analytical technique. The result of this study shows that work satisfaction is able to be intervening variable; employee engagement and competency  positively significantly influence work satisfaction; and employee engagement, competency, and work satisfaction  positively significantly influence employee performance. Keywords: Employee engagement, competency, work satisfaction, employee performance